Notch suppresses angiogenesis and progression of hepatic metastases - Banerjee, Debarshi (Cancer Res, 2015)
The Notch pathway plays multiple key roles in tumorigenesis, and its signaling components have therefore aroused great interest as targets for emerging therapies. Here we show that inhibition of Notch, using a soluble receptor Notch1 decoy, unexpectedly caused a remarkable increase in liver metastases from neuroblastoma and breast cancer cells. Increased liver metastases were also seen after treatment with the γ-secretase inhibitor PF-03084014. Transgenic mice with heterozygous loss of Notch1 demonstrated a marked increase in hepatic metastases, indicating that Notch1 signaling acts as metastatic suppressor in the liver microenvironment. Inhibition of DLL1/4 with ligand-specific Notch1 decoys increased sprouting of sinusoidal endothelial cells into micrometastases, thereby supporting early metastatic angiogenic growth. Inhibition of tumor-derived JAG1 signaling activated hepatic stellate cells, increasing their recruitment to vasculature of micrometastases, thereby supporting progression to macrometastases. These results demonstrate that inhibition of Notch causes pathological activation of liver stromal cells, promoting angiogenesis and growth of hepatic metastases. Our findings have potentially serious implications for Notch inhibition therapy.